Limited attention, marital events and hedge funds - LU, Yan (Institutional Knowledge at Singapore Management University, 2016)
We explore the impact of limited attention by analyzing the performance of hedge fund managers who are distracted by marital events. We find that marriages and divorces are associated with significantly lower fund alpha, during the six-month period surrounding and the two-year period after the event. Busy managers who manage multiple funds and who are not part of a team are more affected by marital transitions. Inattentive managers place fewer active bets relative to their style peers, load more on index stocks, exhibit higher R-squareds with respect to systematic factors, and are more prone to the disposition effect.